1965
DOI: 10.21236/ad0467446
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Boundary Layer Control by Liquid Hydrogen Cryopumping

Abstract: When U. S. Government drawings specifications, or other data arc used for any purpose other than a definitely related Government procurement operation, the Government thereby incurs no responsibility nor any obligation whatsoever, and thn fact that the Government may have formulated, furnished, or in any way supplied the said drawings, specifications, or other data, is not lo be regarded by implication or otherwise, or-in any manner licensing the holder or any other person or corporation, or conveying any righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1966
1966
1972
1972

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Similar data were presented for a stagnation temperature of 300°K in Ref. 2, where it was also shown that the flat plate boundary-layer approximation was accurate to within ±15 percent for a large number of low density nozzles. Within this approximation, then, referring to Fig.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…Similar data were presented for a stagnation temperature of 300°K in Ref. 2, where it was also shown that the flat plate boundary-layer approximation was accurate to within ±15 percent for a large number of low density nozzles. Within this approximation, then, referring to Fig.…”
supporting
confidence: 76%
“…8 of Ref. 2. Such a mode of operation appeared to offer a significant increase in core size over the normal mode of operation with suction, which incorporated a water-cooled throat insert.…”
Section: Performance Of Nozzle With Precooling Of Boundary Layermentioning
confidence: 99%
See 2 more Smart Citations